Alloy cardiovascular stent and surface coating process thereof
Through the multi-layer coating process formed by electrolytic polishing, alkaline heat treatment, polydopamine coating, hyperbranched polymer spraying and nanoparticle coating on the magnesium alloy cardiovascular stent, the rapid degradation of magnesium alloy stent and polymer coating are solved. The problem of poor corrosion resistance has achieved a significant improvement in the corrosion resistance and biocompatibility of the bracket.
Patent Information
- Application Number
- CN202411498025.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The degradation rate of magnesium alloy cardiovascular stent in the human body is too fast, causing the stent to lose its mechanical support prematurely, and the corrosion products produced by degradation cause adverse reactions to surrounding tissues, affecting the vascular remodeling process. At the same time, the polymer coating has poor wetting properties on the magnesium alloy matrix, resulting in unstable corrosion resistance.
Using a multi-layer coating process, the magnesium alloy stent is first electrolytic polished and alkaline heat treatment to form a pretreated magnesium alloy vascular stent, and then a dopamine coating is deposited on its surface, followed by hyperbranched polymers containing amino groups and double bonds. Physical spraying, and finally nanoparticle coating is formed under ultraviolet light, enhancing the corrosion resistance and biocompatibility of the scaffold.
It significantly improves the corrosion resistance and biocompatibility of magnesium alloy stents, extends the mechanical support time of the stent, reduces the corrosion impact on surrounding tissues, enhances antibacterial properties, and improves the safety and effectiveness of clinical applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cardiovascular stents, in particular to an alloy cardiovascular stent and a surface coating process thereof. Background Art
[0002] Alloy cardiovascular stents are important medical devices used to treat cardiovascular diseases. They are usually made of high-strength alloy materials to ensure that they can effectively support blood vessels after implantation to prevent restenosis. With the change of people's lifestyles and the arrival of an aging society, the incidence of cardiovascular diseases has increased year by year. There is an urgent need to develop safer and more effective stent materials and surface coating technologies to improve the biocompatibility and anti-thrombotic ability of stents.
[0003] Titanium alloys, magnesium alloys and other alloys are increasingly used in the development of biomedical materials and devices due to their good mechanical properties and biocompatibility. Biomedical magnesium alloy materials can be degraded and absorbed in the human body, making magnesium alloys a research hotspot in the field of degradable cardiovascular stents in recent years.
[0004] However, the degradation rate of magnesium alloy vascular stents in the human body is too fast, resulting in premature loss of mechanical support of the stent, which limits its clinical application. In addition, the rapid accumulation of corrosion products such as hydrogen and hydroxide ions produced by degradation can also cause adverse reactions to surrounding tissues and affect the vascular remodeling process. Therefore, many works are devoted to improving the corrosion resistance of magnesium alloys through surface coating modification, including metal oxide coatings, fluoride coatings, calcium phosphate coatings, and polymer coatings. Since polymer coatings can serve as drug reservoirs and can be further functionalized with biomolecules, they have additional advantages over other stent coating materials. However, polymer coatings have poor wettability on magnesium alloy substrates. When the surface of magnesium alloy substrates is improved and processed, the coating effect is poor and the adhesion is limited, which ultimately results in poor and unstable corrosion resistance of magnesium alloy substrates. In addition, the rapid precipitation of hydrogen caused by the degradation of the magnesium substrate may lead to the formation of cavitation under the coating, which in turn causes polymer fragments to peel off from the stent, resulting in adverse consequences for clinical use.
[0005] Therefore, we propose an alloy cardiovascular stent and its surface coating process. Summary of the invention
[0006] The purpose of the present invention is to provide an alloy cardiovascular stent and a surface coating process thereof to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A surface coating process for an alloy cardiovascular stent comprises the following steps:
[0009] Step S1: electropolishing, washing, and drying the magnesium alloy vascular stent, immersing it in a sodium hydroxide solution, and treating it at 50-60° C. for 22-24 hours, and obtaining a pretreated magnesium alloy vascular stent after washing and drying;
[0010] Step S2: adjusting the pH of the Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine solution; immersing the pretreated magnesium alloy vascular stent in the dopamine solution, reacting at 35-40° C. for 22-24 hours to form a polydopamine coating, and washing and drying to obtain a polydopamine-modified magnesium alloy vascular stent;
[0011] Step S3: preparing a polymer coating on the surface of the polydopamine-modified magnesium alloy vascular stent by a physical spraying method to obtain a polymer-modified magnesium alloy vascular stent;
[0012] Step S4: immersing the polymer-modified magnesium alloy vascular stent in a nanoparticle solution and irradiating it with ultraviolet light to form a nanoparticle coating, which is then washed and dried to obtain the stent.
[0013] Furthermore, in step S1, the process conditions of electrolytic polishing are: electrolytic polishing for 4-6 minutes at a voltage of 10-12V and a current of 0.2-0.5A.
[0014] Furthermore, in step S1, the concentration of the sodium hydroxide solution is 1-2 mol / L.
[0015] Furthermore, in step S2, the concentration of the Tris-HCl buffer is 0.01 mol / L, and the concentration of the dopamine solution is 3-5 g / L.
[0016] Furthermore, in step S3, the preparation method of the spraying liquid by the physical spraying method is as follows:
[0017] Step (1): 2-methylene-1,3-dioxepane, ethyl 3-aminocrotonate, diethylene glycol divinyl ether, 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl) propionic acid, azobisisobutyronitrile and 1,4-dioxane are mixed uniformly, degassed through three freeze-vacuum-thaw cycles, filled with nitrogen, reacted at 70-80° C. for 22-24 hours, cooled to room temperature, precipitated and dried to obtain a hyperbranched polymer;
[0018] Step (2): Mix the hyperbranched polymer and dichloromethane evenly to obtain a spraying liquid.
[0019] Furthermore, in the step (1), the hyperbranched polymer comprises the following components by weight: 3-5 parts of 2-methylene-1,3-dioxepane, 2.5-3.0 parts of ethyl 3-aminocrotonate, 8-10 parts of diethylene glycol divinyl ether, 1-2 parts of 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl)propionic acid, 0.1-0.3 parts of azobisisobutyronitrile, and 100-110 parts of 1,4-dioxane.
[0020] Furthermore, in step (2), the concentration of the spraying liquid is 5-15wt%.
[0021] In the above technical scheme, 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl) propionic acid is used as a RAFT agent and azobisisobutyronitrile is used as an initiator. The main chain degradable hyperbranched polymer is prepared by free radical ring-opening copolymerization (rROP) of 2-methylene-1,3-dioxepane, 3-amino ethyl crotonate and diethylene glycol divinyl ether, and amino groups and a small amount of unreacted vinyl ether double bonds are introduced into the side chains. The amino groups can react with the polydopamine coating to form a Schiff base reaction to enhance the corrosion resistance of the coating, and the double bonds can form a cross-linked network in the subsequent post-photocuring process to enhance the adhesion of the coating.
[0022] Furthermore, the thickness of the polymer coating is 10-50 μm.
[0023] Furthermore, in step S4, the preparation method of the nanoparticle solution is as follows:
[0024] Step A: Malic acid and deionized water are mixed evenly, treated at 200-210° C. for 5-6 hours, cooled to room temperature, and centrifuged and dialyzed to obtain carbon dots;
[0025] Step B: Disperse chitosan in deionized water, add hydrochloric acid to adjust the pH to 6-7, then add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine and mix well, react in the dark for 22-24 hours, dialyze and dry to obtain thiolated chitosan;
[0026] The hyaluronic acid, carbon dots and deionized water were mixed evenly, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added and mixed evenly, and then thiolated chitosan was added, and the mixture was reacted for 8-10 hours, and nanoparticles were obtained after dialysis and drying;
[0027] Step C: Evenly mix the nanoparticles, the photoinitiator and dichloromethane to obtain a nanoparticle solution.
[0028] In the above technical scheme, malic acid is used as a raw material to prepare carbon dots containing carboxyl groups by a hydrothermal carbonization method; a thiol group is introduced by a condensation reaction between the amino group of chitosan and the carboxyl group of L-cysteine to obtain thiolated chitosan, which also contains an amino group; the carboxyl groups of hyaluronic acid and carbon dots are further reacted with the amino groups of thiolated chitosan to obtain nanoparticles, which can further undergo a thiol-ene click reaction with the double bonds in the polymer coating under the action of a photoinitiator, so that the loading of the nanoparticles is more uniform and firm, thereby enhancing its stability in the coating.
[0029] Furthermore, in step A, the mass ratio of malic acid to deionized water is 1:(20-22).
[0030] Furthermore, in step B, the mass ratio of chitosan, deionized water, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine is 1:100:(7-8):(4.0-4.5):(2-4), and the concentration of hydrochloric acid is 1 mol / L.
[0031] Furthermore, in step B, the mass ratio of hyaluronic acid, carbon dots, thiolated chitosan and deionized water is 1:(0.3-0.5):(2-4):(500-1000).
[0032] Furthermore, in step B, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to N-hydroxysuccinimide is 1:(0.3-0.4), and the mass of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 18-20 times the mass of hyaluronic acid.
[0033] Furthermore, in step C, the mass ratio of the nanoparticles to the photoinitiator is 1:(0.1-0.3), and the concentration of the nanoparticle solution is 0.5-2.0 mg / mL.
[0034] Furthermore, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0035] Furthermore, in step S4, the ultraviolet irradiation process conditions are: irradiation with 360-400nm ultraviolet rays for 30-60min, and an irradiation intensity of 20-35mW / cm 2 .
[0036] Furthermore, the thickness of the nanoparticle coating is 5-20 μm.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. An alloy cardiovascular stent and its surface coating process of the present invention, firstly electrolytically polishing, washing and drying the magnesium alloy stent, and then performing alkaline heat treatment, which preliminarily improves the corrosion resistance of the material to obtain a pretreated magnesium alloy vascular stent; then a layer of polydopamine coating is deposited on the surface of the pretreated magnesium alloy vascular stent as a secondary modification platform, which effectively solves the problem that the metal stent is too stable and difficult to be directly modified;
[0039] Subsequently, a polymer coating is prepared on the surface of the polydopamine-modified magnesium alloy vascular stent. The polymer is a hyperbranched polymer containing amino groups and double bonds. The amino groups of the polymer coating can react with the polydopamine coating to produce a Schiff base reaction, further improving the corrosion resistance of the material.
[0040] Chitosan (CS) is a product produced by removing part of the acetylation of the natural polysaccharide chitin. It has excellent biocompatibility, biodegradability, antibacterial properties, non-toxicity and osteoconductivity; hyaluronic acid (HA) is an important component of the extracellular matrix, which has good anticoagulant, antiproliferative, anti-inflammatory and endothelial cell growth promoting effects; carbon dots (CDs) are a type of carbon-based nanomaterials with a size of less than 10 nanometers, which have excellent corrosion inhibition. Finally, the carboxyl groups of hyaluronic acid and carbon dots are further reacted with the amino groups of thiolated chitosan to obtain nanoparticles; under the action of a photoinitiator, the thiol groups in the nanoparticles react with the double bonds in the polymer coating to undergo a thiol-ene click reaction, so that the nanoparticles are loaded on the polymer coating to form a nanoparticle coating, which not only significantly improves the corrosion resistance of the magnesium alloy stent, but also improves its biocompatibility. At the same time, nanoparticles can act as drug carriers and enhance the therapeutic effect by covalently binding with drugs. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The magnesium alloy vascular stent in this embodiment is of grade AZ31, with an outer diameter of 3 mm and a wall thickness of 0.2 mm.
[0043] In the following examples and comparative examples, 1 part is equal to 10 g.
[0044] Example 1: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0045] Step S1: electropolishing the magnesium alloy vascular stent (electropolishing for 4 min at a voltage of 10 V and a current of 0.2 A), washing, and drying the stent, and then immersing the stent in a 1 mol / L sodium hydroxide solution at 50° C. for 22 h, and washing and drying the stent to obtain a pretreated magnesium alloy vascular stent;
[0046] Step S2: adjusting the pH of 0.01 mol / L Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 3 g / L dopamine solution; immersing the pretreated magnesium alloy vascular stent in the dopamine solution, reacting at 35° C. for 22 hours to form a polydopamine coating, and obtaining a polydopamine-modified magnesium alloy vascular stent after washing and drying;
[0047] Step S3: preparing a polymer coating on the surface of the polydopamine-modified magnesium alloy vascular stent by a physical spraying method to obtain a polymer-modified magnesium alloy vascular stent;
[0048] Step S4: immerse the polymer-modified magnesium alloy stent in the nanoparticle solution and irradiate with 360nm ultraviolet light for 30min with an irradiation intensity of 20mW / cm 2 , forming a nanoparticle coating, which is then washed and dried to obtain;
[0049] In step S3, the preparation method of the spraying liquid of the physical spraying method is as follows:
[0050] Step (1): 3 parts of 2-methylene-1,3-dioxepane, 2.5 parts of ethyl 3-aminocrotonate, 8 parts of diethylene glycol divinyl ether, 1 part of 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl)propionic acid, 0.1 parts of azobisisobutyronitrile and 100 parts of 1,4-dioxane are mixed uniformly, degassed through three freeze-vacuum-thaw cycles, filled with nitrogen, reacted at 70° C. for 22 hours, cooled to room temperature, precipitated and dried to obtain a hyperbranched polymer;
[0051] Step (2): uniformly mixing the hyperbranched polymer and dichloromethane to obtain a 5 wt % spray solution;
[0052] In step S4, the preparation method of the nanoparticle solution is as follows:
[0053] Step A: 0.3 parts of malic acid and 6 parts of deionized water were mixed evenly, treated at 200°C for 5 hours, cooled to room temperature, centrifuged and dialyzed to obtain carbon dots;
[0054] Step B: Disperse 2 parts of chitosan in 200 parts of deionized water, add 1 mol / L hydrochloric acid to adjust the pH to 6, then add 14 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 8 parts of N-hydroxysuccinimide and 4 parts of L-cysteine and mix well, react for 22 hours in the dark, dialyze and dry to obtain thiolated chitosan;
[0055] 1 part of hyaluronic acid, 0.3 part of carbon dots and 500 parts of deionized water were mixed evenly, 18 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 5.4 parts of N-hydroxysuccinimide were added and mixed evenly, and then 2 parts of thiolated chitosan were added, reacted for 8 hours, dialyzed and dried to obtain nanoparticles;
[0056] Step C: Mix 1 part of nanoparticles, 0.1 part of photoinitiator and dichloromethane to obtain a 0.5 mg / mL nanoparticle solution.
[0057] Example 2: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0058] Step S1: electropolishing the magnesium alloy vascular stent (electropolishing for 5 min at a voltage of 11 V and a current of 0.3 A), washing, and drying the stent, and then immersing the stent in a 1.5 mol / L sodium hydroxide solution at 55° C. for 23 h, washing, and drying to obtain a pretreated magnesium alloy vascular stent;
[0059] Step S2: adjusting the pH of 0.01 mol / L Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 4 g / L dopamine solution; immersing the pretreated magnesium alloy vascular stent in the dopamine solution, reacting at 37° C. for 23 h to form a polydopamine coating, and obtaining a polydopamine-modified magnesium alloy vascular stent after washing and drying;
[0060] Step S3: preparing a polymer coating on the surface of the polydopamine-modified magnesium alloy vascular stent by a physical spraying method to obtain a polymer-modified magnesium alloy vascular stent;
[0061] Step S4: immerse the polymer-modified magnesium alloy stent in the nanoparticle solution and irradiate it with 380nm ultraviolet light for 40min at an irradiation intensity of 30mW / cm 2 , forming a nanoparticle coating, which is then washed and dried to obtain;
[0062] In step S3, the preparation method of the spraying liquid of the physical spraying method is as follows:
[0063] Step (1): 4 parts of 2-methylene-1,3-dioxepane, 2.8 parts of ethyl 3-aminocrotonate, 9 parts of diethylene glycol divinyl ether, 1.5 parts of 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl)propionic acid, 0.2 parts of azobisisobutyronitrile and 105 parts of 1,4-dioxane are mixed uniformly, degassed through three freeze-vacuum-thaw cycles, filled with nitrogen, reacted at 75° C. for 23 hours, cooled to room temperature, precipitated and dried to obtain a hyperbranched polymer;
[0064] Step (2): mixing the hyperbranched polymer and dichloromethane uniformly to obtain a 10 wt % spray solution;
[0065] In step S4, the preparation method of the nanoparticle solution is as follows:
[0066] Step A: 1 part of malic acid and 21 parts of deionized water were mixed evenly, treated at 205°C for 5.5 hours, cooled to room temperature, centrifuged and dialyzed to obtain carbon dots;
[0067] Step B: Disperse 3 parts of chitosan in 300 parts of deionized water, add 1 mol / L hydrochloric acid to adjust the pH to 6.5, then add 22 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 13 parts of N-hydroxysuccinimide and 9 parts of L-cysteine and mix well, react in the dark for 23 hours, dialyze and dry to obtain thiolated chitosan;
[0068] 1 part of hyaluronic acid, 0.4 part of carbon dots and 800 parts of deionized water were mixed evenly, 19 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 6.6 parts of N-hydroxysuccinimide were added and mixed evenly, and then 3 parts of thiolated chitosan were added, reacted for 9 hours, dialyzed and dried to obtain nanoparticles;
[0069] Step C: Mix 1 part of nanoparticles, 0.2 part of photoinitiator and dichloromethane to obtain a 1 mg / mL nanoparticle solution.
[0070] Embodiment 3: A surface coating process of an alloy cardiovascular stent, comprising the following process:
[0071] Step S1: electropolishing the magnesium alloy vascular stent (electropolishing for 6 min at a voltage of 12 V and a current of 0.5 A), washing, and drying the stent, and then immersing the stent in a 2 mol / L sodium hydroxide solution at 60° C. for 24 h, and washing and drying the stent to obtain a pretreated magnesium alloy vascular stent;
[0072] Step S2: adjusting the pH of 0.01 mol / L Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 5 g / L dopamine solution; immersing the pretreated magnesium alloy vascular stent in the dopamine solution, reacting at 40° C. for 24 h to form a polydopamine coating, and obtaining a polydopamine-modified magnesium alloy vascular stent after washing and drying;
[0073] Step S3: preparing a polymer coating on the surface of the polydopamine-modified magnesium alloy vascular stent by a physical spraying method to obtain a polymer-modified magnesium alloy vascular stent;
[0074] Step S4: immerse the polymer-modified magnesium alloy stent in the nanoparticle solution and irradiate it with 400nm ultraviolet light for 60min at an irradiation intensity of 35mW / cm 2 , forming a nanoparticle coating, which is then washed and dried to obtain;
[0075] In step S3, the preparation method of the spraying liquid of the physical spraying method is as follows:
[0076] Step (1): 5 parts of 2-methylene-1,3-dioxepane, 3.0 parts of ethyl 3-aminocrotonate, 10 parts of diethylene glycol divinyl ether, 1-2 parts of 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl)propionic acid, 0.1-0.3 parts of azobisisobutyronitrile and 100-110 parts of 1,4-dioxane are mixed uniformly, degassed through three freeze-vacuum-thaw cycles, filled with nitrogen, reacted at 70-80° C. for 22-24 hours, cooled to room temperature, precipitated and dried to obtain a hyperbranched polymer;
[0077] Step (2): uniformly mixing the hyperbranched polymer and dichloromethane to obtain a 15 wt % spray solution;
[0078] In step S4, the preparation method of the nanoparticle solution is as follows:
[0079] Step A: 0.5 parts of malic acid and deionized water were mixed evenly, treated at 210°C for 6 hours, cooled to room temperature, centrifuged and dialyzed to obtain carbon dots;
[0080] Step B: Disperse 4 parts of chitosan in 400 parts of deionized water, add 1 mol / L hydrochloric acid to adjust the pH to 7, then add 32 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 18 parts of N-hydroxysuccinimide and 16 parts of L-cysteine and mix well, react in the dark for 24 hours, dialyze and dry to obtain thiolated chitosan;
[0081] 1 part of hyaluronic acid, 0.5 part of carbon dots and 1000 parts of deionized water were mixed evenly, 20 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 8 parts of N-hydroxysuccinimide were added and mixed evenly, and then 4 parts of thiolated chitosan were added, reacted for 10 hours, dialyzed and dried to obtain nanoparticles;
[0082] Step C: The nanoparticles, photoinitiator and dichloromethane were mixed evenly to obtain a 2 mg / mL nanoparticle solution.
[0083] Comparative Example 1: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0084] Compared with Example 2, Comparative Example 1 does not include step S2, and the other steps are the same as those of Example 2.
[0085] Comparative Example 2: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0086] Compared with Example 2, Comparative Example 2 does not include step S3, and the other steps are the same as those of Example 2.
[0087] Comparative Example 3: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0088] Compared with Example 2, Comparative Example 3 does not include step S4, and the other steps are the same as those of Example 2.
[0089] Comparative Example 4: A surface coating process for an alloy cardiovascular stent, comprising the following processes:
[0090] In step S4, the preparation method of the nanoparticle solution is as follows:
[0091] Step A: 1 part of malic acid and 21 parts of deionized water were mixed evenly, treated at 205°C for 5.5 hours, cooled to room temperature, centrifuged and dialyzed to obtain carbon dots;
[0092] Step B: Disperse 3 parts of chitosan in 300 parts of deionized water, add 1 mol / L hydrochloric acid to adjust the pH to 6.5, then add 22 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 13 parts of N-hydroxysuccinimide and 9 parts of L-cysteine and mix well, react in the dark for 23 hours, dialyze and dry to obtain thiolated chitosan;
[0093] 1 part of hyaluronic acid, 0.4 parts of carbon dots and 800 parts of deionized water were mixed evenly, 19 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 6.6 parts of N-hydroxysuccinimide were added and mixed evenly, and then 0.5 parts of thiolated chitosan were added, reacted for 9 hours, dialyzed and dried to obtain nanoparticles;
[0094] Step C: Mix 1 part of nanoparticles, 0.2 part of photoinitiator and dichloromethane to obtain a 1 mg / mL nanoparticle solution;
[0095] Compared with Example 2, in step B of Comparative Example 4, the mass ratio of hyaluronic acid, carbon dots and thiolated chitosan is 1:0.4:0.5, and the other steps are the same as those in Example 2.
[0096] Experiment: The magnesium alloy cardiovascular stents prepared in Examples 1-3 and Comparative Examples 1-4 were used to prepare samples, and their properties were tested and the test results were recorded:
[0097] Water contact angle test: The water contact angle on the sample surface was measured by a Powereach JC2000C contact angle goniometer, and the volume of a single water droplet was 5 μL.
[0098] Immersion weight loss test: The samples were immersed in Hank's dynamic simulated body fluid for 288 hours, then cleaned with 180g / L chromic acid solution to remove corrosion products, and then reweighed. The corrosion resistance of different samples was evaluated by calculating the corrosion rate.
[0099] Antibacterial test: Place the samples in marked centrifuge tubes and sterilize them. Then add activated bacteria and LB broth. Place the centrifuge tubes in a constant temperature shaker (37°C) and incubate for 24 hours. Then use a pipette to draw an appropriate amount of liquid from the centrifuge tubes and dilute it by 10 5 Then, use a pipette to draw 5 μL, drop it on the culture medium containing agar, and spread the diluted liquid evenly with a glass rod that has been sterilized by an alcohol lamp. Then seal the culture medium and place it in a constant temperature incubator for 24 hours. Then count the number of colonies and calculate the antibacterial rate. The bacteria tested in the experiment were Staphylococcus aureus.
[0100] In vitro biocompatibility experiment: Mouse calvaria preosteoblasts (MC3T3-E1) cultured in a cell culture incubator at 37°C and 5% CO2 concentration were selected. The complete culture medium (DMEM) containing 1% penicillin, streptomycin and 10% fetal bovine serum (FBS) was replaced every 48 hours. When the cells grew to 80-90% confluence, they were subcultured. The third to sixth generations of cells were used for the experiment. The sterilized samples were placed at 1.25 cm 2 / mL was placed in DMEM at 37°C for 24 hours to obtain an extract, which was stored at 4°C for later use. To allow cells to attach, a 96-well plate (2×10 4Cells / mL) were placed in a cell culture incubator for 24 hours, and then DMEM was replaced with the extract and continued to be cultured. After 3 days, the extract was removed and DMEM containing 10% CCK-8 was added to the well plate. After 2 hours of incubation, the absorbance was measured at 450nm using a microplate spectrophotometer (Biotek, USA), and the cell survival rate was calculated. Cell survival rate (100%) = (AB) / (CB) × 100%, A corresponds to the absorbance of each sample group; B corresponds to the blank group, that is, the absorbance of the complete culture medium; C corresponds to the negative control group, that is, the absorbance of the complete culture medium containing cells.
[0101] The test results are as follows:
[0102] Water contact angle (°) Corrosion rate (mm / y) Antibacterial rate / % Cell survival rate / % Example 1 60 0.12 98.8 93 Example 2 56 0.08 99.5 95 Example 3 58 0.10 99.2 94 Comparative Example 1 75 0.15 96.7 90 Comparative Example 2 78 0.22 94.5 85 Comparative Example 3 67 0.18 85.6 88 Comparative Example 4 64 0.13 97.3 92
[0103] According to the data in the above table, we can clearly draw the following conclusions:
[0104] 1. Compared with Examples 1-3, the water contact angle and corrosion rate of the products obtained in Comparative Examples 1, 2 and 3 increased, while the antibacterial rate and cell survival rate decreased, indicating that under the synergistic effect of the multi-layer coating of the polydopamine coating, polymer coating and nanoparticle coating in the present invention, the stent exhibits stronger hydrophilicity and corrosion resistance, and significantly improves its antibacterial and biocompatibility.
[0105] 2. Compared with Examples 1-3, the water contact angle and corrosion rate of the product obtained in Comparative Example 4 increased, while the antibacterial rate and cell survival rate decreased. It can be seen that when the amount of thiolated chitosan added is reduced, the hydrophilicity, corrosion resistance, antibacterial property and biocompatibility of the material will decrease. Therefore, the performance of the nanoparticles prepared by the present invention is affected by the ratio of each reagent in its preparation process, and a mass ratio within the range is selected to achieve a more excellent performance effect.
[0106] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A surface coating process for an alloy cardiovascular stent, characterized in that: The steps include: Step S1: electropolishing, washing, and drying the magnesium alloy vascular stent, immersing it in a sodium hydroxide solution, and treating it at 50-60° C. for 22-24 hours, and obtaining a pretreated magnesium alloy vascular stent after washing and drying; Step S2: adjusting the pH of the Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine solution; immersing the pretreated magnesium alloy vascular stent in the dopamine solution, reacting at 35-40° C. for 22-24 hours to form a polydopamine coating, and washing and drying to obtain a polydopamine-modified magnesium alloy vascular stent; Step S3: preparing a polymer coating on the surface of the polydopamine-modified magnesium alloy vascular stent by a physical spraying method to obtain a polymer-modified magnesium alloy vascular stent; Step S4: immersing the polymer-modified magnesium alloy vascular stent in a nanoparticle solution and irradiating it with ultraviolet light to form a nanoparticle coating, which is then washed and dried to obtain the stent.
2. The surface coating process of an alloy cardiovascular stent according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 1-2 mol / L.
3. The surface coating process of an alloy cardiovascular stent according to claim 1, characterized in that: In step S2, the concentration of the Tris-HCl buffer is 0.01 mol / L, and the concentration of the dopamine solution is 3-5 g / L.
4. The surface coating process of an alloy cardiovascular stent according to claim 1, characterized in that: In step S3, the preparation method of the spraying liquid of the physical spraying method is as follows: Step (1): 2-methylene-1,3-dioxepane, ethyl 3-aminocrotonate, diethylene glycol divinyl ether, 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl) propionic acid, azobisisobutyronitrile and 1,4-dioxane are mixed uniformly, degassed through three freeze-vacuum-thaw cycles, filled with nitrogen, reacted at 70-80° C. for 22-24 hours, cooled to room temperature, precipitated and dried to obtain a hyperbranched polymer; Step (2): Mix the hyperbranched polymer and dichloromethane evenly to obtain a spraying liquid.
5. The surface coating process of an alloy cardiovascular stent according to claim 4, characterized in that: In the step (1), the hyperbranched polymer comprises the following components by weight: 3-5 parts of 2-methylene-1,3-dioxepane, 2.5-3.0 parts of ethyl 3-aminocrotonate, 8-10 parts of diethylene glycol divinyl ether, 1-2 parts of 2-(2-carboxyethylsulfanylthiocarbonylsulfanyl)propionic acid, 0.1-0.3 parts of azobisisobutyronitrile, and 100-110 parts of 1,4-dioxane.
6. The surface coating process of an alloy cardiovascular stent according to claim 4, characterized in that: In the step (2), the concentration of the spraying liquid is 5-15wt%.
7. The surface coating process of an alloy cardiovascular stent according to claim 1, characterized in that: In step S4, the preparation method of the nanoparticle solution is as follows: Step A: Malic acid and deionized water are mixed evenly, treated at 200-210° C. for 5-6 hours, cooled to room temperature, and centrifuged and dialyzed to obtain carbon dots; Step B: Disperse chitosan in deionized water, add hydrochloric acid to adjust the pH to 6-7, then add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine and mix well, react in the dark for 22-24 hours, dialyze and dry to obtain thiolated chitosan; The hyaluronic acid, carbon dots and deionized water were mixed evenly, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added and mixed evenly, and then thiolated chitosan was added, and the mixture was reacted for 8-10 hours, and nanoparticles were obtained after dialysis and drying; Step C: Evenly mix the nanoparticles, the photoinitiator and dichloromethane to obtain a nanoparticle solution.
8. The surface coating process of an alloy cardiovascular stent according to claim 7, characterized in that: In the step B, the mass ratio of hyaluronic acid, carbon dots, thiolated chitosan and deionized water is 1:(0.3-0.5):(2-4):(500-1000).
9. The surface coating process of an alloy cardiovascular stent according to claim 7, characterized in that: In the step C, the mass ratio of the nanoparticles to the photoinitiator is 1:(0.1-0.3), and the concentration of the nanoparticle solution is 0.5-2.0 mg / mL.
10. The surface coating process of an alloy cardiovascular stent according to claim 1, characterized in that: In step S4, the ultraviolet irradiation process conditions are: irradiation with 360-400nm ultraviolet rays for 30-60min, and irradiation intensity of 20-35mW / cm 2 .
Citation Information
Patent Citations
Method for bonding carboxymethyl chitosan bioactive molecules on surface of magnesium alloy
CN103657996A
High-hydrophobicity silicon carbide foam ceramic as well as preparation method and application thereof
CN107857593A
Tungsten filament containing polydopamine coating as well as preparation method and application of tungsten filament
CN118059320A
Stent made of a biodegradable magnesium alloy with a magnesium fluoride coding and an organic coating
EP3342433A1
Cited By
Photosensitive tyramine-sulfonated hyaluronic acid microspheres as well as preparation method and application thereof
CN120365453A